A. Busilas education ideas in inter-war Lithuania periodicals and methodology of mathematics - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2015)
The article analyzed the educational ideas of the interwar Lithuania periodicals and methodology by A.Busilas. A.Busilas laboratory provides the basic principles of teaching mathematics.